Model Value of Taiji Curve Algorithm in Economic Geographic and Natural Game Management Information System - Chengqi Xu; Kegong Chen (Journal of Mathematics)
In order to study the role of tai chi curve algorithm in economic geography and natural ecological management and explore the application value of tai chi curve algorithm and its model, this study discusses the principle of Chinese tai chi diagram, using mathematical model construction method by the previous tai chi map and Pythagoras theorem clever results, produced the tai chi graph s curve algorithm, and discusses the application value of tai chi curve algorithm and its model from different angles; this study takes Zhangye geography as an example, which provides an applied research direction for the future scientific research of Chinese economic geography and also provides a clever connection with ecological correlation and nature; finally, it is found that the Taiji graph s curve algorithm can calculate the corresponding Yin and Yang values according to the balance point and relative deviation amount of the attribute state, and the results have an extraordinary influence in economic geography, information management system, natural ecology, and other aspects.